Turnover Intention and Procrastination: Causal Contribution of Work-Life (Im)Balance - Sharma, Abhishek; Sharma, Ankita (The journal of contemporary issues in business and government, 2021)
In the changing world of work, including increasing working parents and work from home, work-life balance is receiving increased attention from HR executives looking to improve employee productivity. Talent retention and getting active and responsible contributions from existing employees are permanent concern for organizations because of their high costs and negative consequences. This research aims to investigate the relationship of work-life balance with turnover intention and procrastination. The present study was conducted with 104 office staff working in various business organizations. The results showed a significant relationship between work-life balance and turnover intention and a significant relationship between work-life balance and procrastination. Further regression analysis showed a significant prediction of turnover intention and procrastination by work- life balance. The study’s results suggested that work-life balance provisions should be included in organization policy and talent retention strategies.